Anti-Diabetic Effects of Oleuropein - Michael Iantomasi; Matthew Terzo; Evangelia Tsiani (Metabolites)
Background/Objectives: Oleuropein, a secoiridoid polyphenol found in olive oil as well as the fruit and leaves of the olive tree, has been reported to have antioxidant, cardioprotective, anti-inflammatory, anti-cancer, and anti-diabetic properties. Type 2 diabetes mellitus (TD2M) is a chronic metabolic disease characterized by impaired insulin action, termed insulin resistance. The development of T2DM is closely associated with obesity and chronic low-grade inflammation. In recent years, a rise in sedentary lifestyles and diets rich in refined carbohydrates and saturated fats has contributed to an increase in the prevalence of obesity and TD2M. Currently, the strategies for treating T2DM and its prevention lack efficacy and are associated with adverse side effects. Hence, there is an urgent need for novel treatment strategies, including naturally occurring compounds possessing hypoglycemic and insulin-sensitizing properties. Methods: This review summarizes the evidence of the anti-inflammatory and anti-diabetic properties of oleuropein from in vitro and in vivo animal studies, as well as the available clinical trials. Results: The existing evidence indicates that oleuropein may exert its anti-inflammatory effects by downregulating the levels of pro-inflammatory cytokines in hepatic and adipose tissue. Additionally, the evidence suggests that oleuropein targets skeletal muscle and enhances glucose uptake and its related protein signalling cascades, improving glucose tolerance and insulin sensitivity. Conclusions: Despite the evidence of oleuropein’s anti-inflammatory and anti-diabetic potential, more animal and clinical studies are needed to proceed towards its clinical/therapeutic use for metabolic diseases confidently.